2009
DOI: 10.1002/app.29985
|View full text |Cite
|
Sign up to set email alerts
|

Determination of crystallinity ratio and some physicochemical properties of poly(4‐methyl‐1‐pentene)

Abstract: It was determined that the thermal stability of poly(4-methyl-1-pentene) (P4MP) was maintained up to 424 C in an inert atmosphere by thermogravimetric analysis. The retention diagrams of ethyl acetate, tert-butyl acetate, and benzene on P4MP were plotted at temperatures between 30 and 280 C by inverse gas chromatography (IGC) technique. Melting temperature of the polymer was determined as 230 and 239.5C by IGC and differential scanning calorimetry (DSC), respectively. The percent crystallinity of P4MP was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In other words, a low χ12 value reflects good compatibility. The following rules have been developed for the system [29,30]: an χ12 value that is lower than 0.5 indicates that the solvent is good, and a value of between 0.5 and 1 indicates a moderately suitable solvent, whereas a χ12 value that is larger than 1 indicates a poor solvent. The results are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, a low χ12 value reflects good compatibility. The following rules have been developed for the system [29,30]: an χ12 value that is lower than 0.5 indicates that the solvent is good, and a value of between 0.5 and 1 indicates a moderately suitable solvent, whereas a χ12 value that is larger than 1 indicates a poor solvent. The results are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, a relatively new methodology, based on inverse gas chromatography (IGC) measurements, is being recently employed to determine the crystallinity ratio. Although IGC measurements have been widely employed to study polymer-solvent interactions, its use to determine the crystallinity of a polymeric material is relatively new [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the interactions between alkanes and iron oxide samples can become favourable with the increase of amorphous site of iron oxide samples at lower iron ion amount. This result can open a new research field on determination of crystallinity of inorganic particles by inverse gas chromatography, like polymers 51,52 . As expected, the iron oxide nanoparticles are of basic character by increasing with base concentration but decreasing with iron salt concentration.…”
Section: Resultsmentioning
confidence: 78%